Automated Smoothie Maker - et. al., R. Krishna Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Automation is a common subject in the twenty-first century, and it has become increasingly important in our everyday lives. The key benefit of any automated system is that it reduces human labor, effort, time, and errors caused by human error. The food and beverage industry has undergone major transformations in favor of healthier goods, especially smoothies. Customers are expecting fresher, higher-quality goods as a result of these improvements. Convenient stores have ready-to-eat options. The lack of natural options available in convenience stores, on the other hand, is a concern. This revealed a previously untapped market for the creation of a system capable of making ready-to-drink natural fruit smoothies. Throughout this study, a five-step concept creation process was used to address the best arrangement of pieces, as well as details design and recommendations for further analysis. It can be inferred that the smoothie machine built in this project represents a significant business opportunity, as there are virtually no technologies that serve this growing market at convenient stores.Our project has advanced due to changes in the design and process phases. This digital machine would be beneficial to most people who operate on a tight schedule and find it difficult to maintain a healthy diet. The system's performance can be improved even further with advances in Nanotechnology and Material Science.